Anti-annexin antibodies, cholesterol levels and disability in multiple sclerosis. (8th October 2015) - Mandoj, Chiara; Renna, Rosaria; Plantone, Domenico; Sperduti, Isabella; Cigliana, Giovanni; Conti, Laura; Koudriavtseva, Tatiana
Highlights: Abnormal cholesterol homeostasis might contribute to MS progression. Anti annexin-V Abs correlate with total and LDL-cholesterol levels. Annexin-V is a calcium-dependent glycoprotein with a potent anticoagulant activity. The cholesterol effect on MS disability may be related to thrombogenic mechanisms. Abstract: So far, no studies have been conducted to evaluate possible correlations between lipid/lipoprotein levels and the anti-phospholipid antibody (aPL) positivity in multiple sclerosis (MS). In this cross-sectional study, we aimed to investigate the relationships between serum lipid profile and aPL positivity rates in MS patients, and their possible differences among secondary-progressive MS (SPMS) patients, relapsing–remitting MS patients in remission (REM) and in relapse (REL). We included 16 SPMS, 58 REM and 26 REL. Their sera were tested for aPL (anti-cardiolipin, anti-β2glycoproteinI, anti-prothrombin, anti-annexinV), total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), triglycerides (TG) and lipoprotein(a) levels. High TC levels were more frequent in SPMS patients than other groups ( p = 0.05). The REL had significantly higher rates of positivity for anti-β2glycoproteinI IgM ( p < 0.0001), anti-prothrombin IgG and IgM (both p = 0.05) than the other groups. A significant positive correlation was found between age and both TC and LDL-C, disability and both TC and LDL-C, disease duration and LDL-C. TC levels were significantly higher ( p = 0.007) in anti-annexinV-IgG positive patients. The anti-annexinV-IgG positivity significantly associated with high levels of TC ( p = 0.002) and LDL-C ( p = 0.03). Our results support the hypothesis that both thrombogenic and neurodegenerative mechanisms associated with an abnormal cholesterol homeostasis might contribute to MS progression. Our study may have interesting practical implications, which could potentially open new therapeutic approaches in the context of appropriately designed clinical trials.